Pemberdayaan Masyarakat Terdampak Covid-19 melalui Penguatan Aspek Manajemen dan Teknologi Pemasaran bagi UKM - Ismet Sulila (Jurnal Pengabdian Pada Masyarakat, 2021)
EMPOWERING COMMUNITIES AFFECTED BY COVID-19 THROUGH STRENGTHENING MANAGEMENT ASPECTS AND MARKETING TECHNOLOGY FOR SMES. In Gorontalo Province the Covid 19 pandemic has been going on for approximately one year. One of the affected areas is North Gorontalo District, which is directly adjacent to the Provinces of Central Sulawesi and the Provinces of North Sulawesi. This area has a lot of potential unmanaged marine resources. One of them is the great potential of seaweed. In this region, the level of seaweed production reaches ± 28,866 tons / year. Of this amount, only about 20% is used by local processing industries as food processing materials, while 80% is sent to processing factories in Manado, Makassar and Surabaya. This happens because of two things: 1) the implementation of functions and elements of management has not been maximized, 2) there is no concept of developing centers and group coaching. Therefore, assistance from related parties, including universities in management technology transfer and standardization of product processing diversification for the development of SME centers is highly expected. In general, the purpose of this activity is to reduce the negative impact of the spread of covid 19, especially for the community of seaweed SMEs in Katialada village. The method used is technical guidance for the diversification of processed seaweed management and assistance in implementing functions and elements of management, industrialization and product standardization as well as the development of processed products to local and national markets. The results of this service are expected to increase economic added value for coastal community groups who are directly affected by Covid 19.